The economic consequences of Brain Drain of the best and brightest: Microeconomic evidence from five countries - John Gibson; David McKenzie (Institute for the Study of Labor (IZA), 2010)
Brain drain has long been a common concern for migrant-sending countries, particularly for small countries where high-skilled emigration rates are highest. However, while economic theory suggests a number of possible benefits, in addition to costs, from skilled emigration, the evidence base on many of these is very limited. Moreover, the lessons from case studies of benefits to China and India from skilled emigration may not be relevant to much smaller countries. This paper presents the results of innovative surveys which tracked academic high-achievers from five countries to wherever they moved in the world in order to directly measure at the micro level the channels through which high-skilled emigration affects the sending country. The results show that there are very high levels of emigration and of return migration among the very highly skilled; the income gains to the best and brightest from migrating are very large, and an order of magnitude or more greater than any other effect; there are large benefits from migration in terms of postgraduate education; most high-skilled migrants from poorer countries send remittances; but that involvement in trade and foreign direct investment is a rare occurrence. There is considerable knowledge flow from both current and return migrants about job and study opportunities abroad, but little net knowledge sharing from current migrants to home country governments or businesses. Finally, the fiscal costs vary considerably across countries, and depend on the extent to which governments rely on progressive income taxation.
urn:nbn:de:101:1-201010132799
Keywords: O15; F22; J61; 330; brain drain; brain gain; highly skilled migration